The Analysis of PPG English Teachers' Knowledge in Implementing Genre-Based Approach in Schools - Iasya, Lydia Kusdyanti; Lengkanawati, Nenden Sri; Yusuf, Fazri Nur (Jurnal Pendidikan Humaniora, 2025)
This study examines the effectiveness of the Platform of Emancipated Curriculum (PMM) in supporting professional and pedagogical competencies among English teachers participating in the Piloting 2 batch of the Program of Teachers Professional Education (PPG), which notably removed facilitator-led Zoom meetings. Using a survey research design with data collected via Google Forms from 30 English teachers, the study assessed their understanding of genre-based approaches—particularly those informed by systemic functional linguistics and the Derewianka model. Quantitative findings indicate a moderate grasp of these approaches, while qualitative responses reveal significant challenges in their practical application. Participants also expressed a need for enhanced professional development and better instructional materials. The results offer insights for refining the PPG process and underscore the potential benefits of expanding future research to include larger, more diverse samples and to investigate the impact of targeted programs on teachers’ mastery of genre-based strategies.